2011
DOI: 10.1002/eji.201141814
|View full text |Cite
|
Sign up to set email alerts
|

CD4+Foxp3+ regulatory T cells suppress γδ T‐cell effector functions in a model of T‐cell‐induced mucosal inflammation

Abstract: Foxp31 regulatory T (T REG ) cells are critical mediators of peripheral immune tolerance, and abrogation of their function provokes a variety of autoimmune and inflammatory states including inflammatory bowel disease. In this study, we investigate the functional dynamics of T REG -cell responses in a CD4) hosts to gain insights into the mechanism and cellular targets of suppression in vivo. We show that CD4 1 T effector cell transfer into T-cell-deficient mice rapidly induces mucosal inflammation and colitis d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…These investigators have also reported IL-17 production from innate lymphoid cells in CD patients [62]. As a whole, these data suggest that innate lymphoid cell populations could initiate early intestinal inflammation in patients with IBD; and be amenable to pharmacological manipulation, particularly in the context of prophylactic/maintenance therapies (see the earlier discussion) [8,[57][58][59][60][61][62][63]. In support of this possibility, our laboratory has shown that colonic STAT3 activation and IL-17 secretion occur during TNBS-induced colits and can be inhibited by Vidofludimus [8,24].…”
Section: Il-17 Inhibition and Ibd mentioning
confidence: 88%
See 1 more Smart Citation
“…These investigators have also reported IL-17 production from innate lymphoid cells in CD patients [62]. As a whole, these data suggest that innate lymphoid cell populations could initiate early intestinal inflammation in patients with IBD; and be amenable to pharmacological manipulation, particularly in the context of prophylactic/maintenance therapies (see the earlier discussion) [8,[57][58][59][60][61][62][63]. In support of this possibility, our laboratory has shown that colonic STAT3 activation and IL-17 secretion occur during TNBS-induced colits and can be inhibited by Vidofludimus [8,24].…”
Section: Il-17 Inhibition and Ibd mentioning
confidence: 88%
“…Sutton et al demonstrated that IL-17 production was mainly from ‫ץ‬δ T-cells [58,59]. Recently, other investigators suggested a prominent role for resident ‫ץ‬δ T-cells in promoting Th1 and Th17 responses in the early phase of colitis in mice [60]. Also, International Reviews of Immunology Int Rev Immunol Downloaded from informahealthcare.com by Universitat de Girona on 11/20/14…”
Section: Il-17 Inhibition and Ibd mentioning
confidence: 97%
“…gdT17 cells have most recently been shown to participate in the immunopathology of a variety of inflammatory diseases in epithelial barrier tissues, including inflammatory bowel disease, psoriasis, and asthma (11,14,15), but also in spondylarthropathies and CNS inflammation in mouse models (1,16) and in humans (17)(18)(19). Because the presence of gdT17 cells in certain tissues might set the threshold for these tissues to respond directly to pathogen-associated molecular patterns and indirectly to the proinflammatory cytokine IL-23, the regulation of gdT17 cell populations during homeostasis and in inflammation is highly relevant in the context of immune interventions in autoimmune diseases, chronic inflammation, and inflammation associated with malignant disease.…”
mentioning
confidence: 99%
“…In the battle against infectious pathogens, the activity of cd-T cells is also regulated by other molecules that act through multiple pathways. It has been confirmed that both murine 122 and human 123 CD4 1 Tregs can directly suppress the expansion and cytokine production of mucosal cd-T cells, whereas effector CD4 1 T cells help maintain IL-17 production in cd-T cells in naive animals. 124 These dynamic interactions exist not only between adaptive immunity and innate immunity, but also within the innate immune system itself.…”
Section: Regulation Of Cd-t-mediated Anti-infection Responsesmentioning
confidence: 95%